Armazenamento de sementes de caviúna-do-cerrado (Dalbergia miscolobium Benth - Fabaceae) - Santos, Renata Moreira dos (2022)
Seed storage is a method of ex situ conservation of species and also a way to ensure less seasonality or low supply of seedling production. For successful storage, it is necessary to choose ideal environments and packaging in order to maintain seed viability for as long as possible. The present work aimed to evaluate the behavior of Dalbergia miscolobium seeds under different storage conditions. It aimed to answer which is the best environment and packaging in which these seeds can be stored. The seeds were stored in three different environments (cold chamber, freezer and environment conditions) and in three packages (plastic bag, paper bag and glass), being evaluated during five periods (15, 30, 45, 75 and 120 days) through test germination (percentage of germination, germination speed index - IVG and mean germination time - TMG), humidity and electrical conductivity. Entirely casualized experimental delineation was adopted, in the factorial scheme 3 (environments) x 3 (packages) x 5 (periods) + additional treatment. The F test that compared the control and the factorial treatments (storage in different packages and environments) showed that the means of germination and electrical conductivity parameters were statistically equal and that humidity, IVG and TMG presented statistical differences. Seed moisture suffered an isolated effect of storage time, with no statistical difference between the periods of 30 and 120 days and between the periods of 45 and 75 days. There was a significant interaction for humidity between the place of storage and the packaging used. The greatest increase in water content was observed in seeds stored in the environment and in paper bags. No significant effect of packaging on germination percentage was observed. The storage location had a significant isolated effect on germination. The effect of the environment and the cold chamber on germination showed no significant difference, showing respectively, 97% and 97,5%, and the freezer was statistically different from the others, with 94,42% of germinated seeds. There was an isolated effect of packaging on IVG and TMG. Electrical conductivity showed significant interactions between location/packaging and location/time. The seeds stored in paper bags in the environment had lower values for electrical conductivity compared to plastic and glass bags, being statistically different. It is concluded that both paper bag, plastic bag and glass can be used in the storage of D. miscolobium seeds. D. miscolobium seeds can be stored enviroments conditions and in a cold chamber. Storage in a paper bag in the environment for a period equal to that evaluated in the present study is recommended.The behavior of D. miscolobium seeds after 120 days of storage shows that they should be classified as orthodox.